Evaluation of estrogenic and anti-estrogenic activity of endocrine disruptors using breast cancer spheroids: a comparative study of T47D and MCF7 cell lines in 2D and 3D models - Barbaro, Katia; Innocenzi, Elisa; Monteleone, Valentina; Marcoccia, Daniele; Altigeri, Annalisa; Zepparoni, Alessia; Caciolo, Daniela; Alimonti, Cristian; Mollari, Marta; Ghisellini, Paola; Rando, Cristina; Eggenhöffner, Roberto; et al. (Frontiers in Toxicology, 2025)
IntroductionThe estrogenic and anti-estrogenic effects of endocrine disruptors were examined in vitro using two-dimensional 2D and three-dimensional 3D estrogen receptor-positive T47D and MCF7 human breast cancer cells.MethodsThe in vitro model system was used to test the plasticizer Bisphenol A (BPA), a known endocrine disruptor (EDs) with estrogen-like action, aga inst 17β-Estradiol (E2), the endogenous nuclear estrogen receptor (nERs) ligand, and the anti-estrogenic drug Fulvestrant (FUL). Spheroid formation and gene expression of estrogen-regulated markers (pS2 and TGFβ3) both in 2D and 3D cultures were used to establish the dose-dependent cellular effects of these substances, evaluated cell viability either by separately treating with the individual substances or in co-treatment.ResultsBPA exhibited a dose-dependent estrogenic activity in both 2D and 3D cultures, significantly influencing cell proliferation and gene expression of estrogen-regulated markers (pS2 and TGFβ3). In contrast, FUL displayed anti-estrogenic properties, effectively inhibiting the proliferative effects of E2, thereby highlighting the complex interactions between these compounds and the nERs pathways in human breast cancer cells.DiscussionOur findings indicate that E2 and BPA significantly increase pS2 expression while decreasing TGFβ3, and that FUL co-treatment reverses these effects. Therefore, the in vitro model system could serve to observe the cell-mediated effects caused by the interaction of EDs with nERs. Through the use of these in vitro model systems - 2D and especially 3D, the latter of which allow better emulation of complex physiological and pathological processes occurring in vivo, the effects caused by EDs on nERs pathways can be detected and studied under various conditions. This approach performs as a preliminary screening tool to identify estrogenic substances, offering the potential to reduce reliance on in vivo experiments and contributing to improved environmental and health risk assessments.